Preparation method and application of biomass-based iron-nitrogen-doped carbon catalyst with full pH range

Through the preparation method of the biomass-based iron-nitrogen doped carbon catalyst, the problem of developing high-efficiency zinc-air battery oxygen reduction electrocatalysts within the entire pH range is solved, and efficient and stable electrocatalytic performance and excellent electrochemical performance of zinc-air battery are achieved.

CN119601674APending Publication Date: 2025-03-11CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311155298.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to develop efficient and stable zinc-air battery oxygen reduction electrocatalysts within the full pH range, especially under acidic and neutral conditions, the Fe-N-C catalyst has poor durability and activity.

Method used

Using the preparation method of a biomass-based iron-nitrogen doped carbon catalyst, layered porous carbon nanofiber blocks are produced by carbonization of bacterial cellulose and ZnFe-MOF. Controllable defects and micropores are generated by Zn2+ gasification and evaporation etching, limiting the growth of iron particles, and improving the specific surface area of ​​the catalyst and electrocatalytic activity within the entire pH range.

Benefits of technology

It achieves efficient and stable electrocatalytic oxygen reduction performance under all pH conditions and exhibits excellent electrochemical properties in zinc-air batteries, including high specific capacity and significant power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601674A_ABST
    Figure CN119601674A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to a preparation method of a biomass-based iron-nitrogen-doped carbon catalyst with a full pH range and application of the biomass-based iron-nitrogen-doped carbon catalyst in the field of zinc-air batteries. According to the preparation method, bacterial cellulose, zinc nitrate, ferric chloride and dimethylimidazole are taken as precursors, a clean, efficient and stable soft template method is selected, and Zn < 2 + > gasification and evaporation etching in a pyrolysis process are utilized, so that the derived carbon catalyst generates a large number of defects and a large number of micropores and mesopores, and overgrowth of iron nanoparticles is limited; and the oxygen reduction catalyst with high specific surface area and high catalytic activity and stability in a whole pH range is prepared through drying and high-temperature carbonization process optimization, so that an electrode active material with excellent electrochemical performance is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of new energy material technology, and specifically relates to a method for preparing a biomass-based iron-nitrogen-doped carbon catalyst with a full pH range and its application in the field of zinc-air batteries. Background Art

[0002] Currently, the increasing shortage of energy and the extensive use of fossil fuels have caused global pollution, deterioration of air quality and energy security. Therefore, new electrochemical energy storage and conversion devices that are environmentally friendly, efficient and sustainable have attracted increasing interest. Zinc-air batteries are a prominent class of energy storage devices due to their high theoretical energy density (1084Whkg -1 ), inherent safety, environmental friendliness, and applicability, and therefore have attracted much attention. The oxygen reduction reaction (ORR) is considered to be the fundamental problem of these clean energy devices, but it faces many difficulties due to its sluggish kinetics, especially in acidic and neutral electrolytes. To date, noble metals (such as Pt) are the state-of-the-art electrocatalysts for reactions in pH-universal media. Unfortunately, the large-scale development of these noble metal catalysts is severely limited due to their scarcity, high cost, unsatisfactory durability, and low activity in the corresponding or reverse reactions. Therefore, in order to create high-performance zinc-air batteries in pH-universal media, people have been working hard to create effective, reliable, and low-cost catalysts.

[0003] Recently, MNC (M=Fe, Ni, Co, etc.) materials have become a hot topic of research due to their good ORR activity, strong interfacial conjugation and ability to adsorb O2. Of particular note, Fe-NC materials have become a leading candidate as an efficient and durable ORR catalyst. Although efficient Fe-NC catalysts comparable to Pt / C catalysts can be prepared, this mostly occurs under alkaline conditions. Therefore, the development of efficient electrocatalysts under acidic conditions or even neutral environments is imminent.

[0004] It has been shown that the durability of Fe-NC molecules degrades when exposed to H2O2 in acidic media. Carbon catalysts gradually degrade, especially when the ORR catalysis is poorly selective for the composite four-proton coupled electron transfer process. In addition, Fe-NC catalysts can also suffer from micropore flooding, demetallization, active site protonation and / or carbon corrosion when used in acidic electrolytes for a long time. More importantly, the ORR activity in neutral environments is usually slow because the ionic conductivity is usually low and the OH- concentration is extremely low. Therefore, it is necessary and desirable to develop Fe-NC ORR catalysts with high activity and good durability under all practical conditions (i.e., in alkaline, acidic and neutral media) for Zn-air batteries.

[0005] Therefore, based on the above discussion, if Fe-NC oxygen reduction electrocatalysts with reasonable mass transfer channels and high-density active sites can be designed using a low-cost, simple, fast and environmentally friendly method, it will be the key to promoting the research and development of carbon-based platinum-substituting catalysts, which will be of great value to the development of fuel cells, metal-air batteries and other oxygen reduction-related fields. Summary of the invention

[0006] The purpose of the present invention is to solve the above-mentioned technical problems and provide a method for preparing a biomass-based iron-nitrogen-doped carbon catalyst, which has high-efficiency and stable electrocatalytic oxygen reduction performance under full pH conditions as an oxygen reduction electrocatalyst and exhibits excellent electrochemical performance in zinc-air batteries.

[0007] The above-mentioned purpose of the present invention is implemented through the following technical solutions:

[0008] A method for preparing an iron-nitrogen doped carbon catalyst based on biomass, wherein the specific surface area of ​​the carbon catalyst is 186-704 m 2-1 , pore volume is 0.10-0.6cm 3 g -1 , pore size is 5-10nm.

[0009] Preferably, the specific surface area of ​​the carbon catalyst is 700-710m 2 g -1 , pore volume is 0.50-0.60cm 3 g -1 , the pore size is 5-6nm.

[0010] The present invention also provides a method for preparing a biomass iron-nitrogen doped carbon catalyst, the method comprising the following steps:

[0011] S1: preparing bacterial cellulose dispersion;

[0012] S2: adding ferric chloride, zinc nitrate and dimethylimidazole into the bacterial cellulose dispersion and stirring evenly;

[0013] S3: centrifugal freeze drying to obtain solid powder;

[0014] S4: High temperature pyrolysis under an inert protective gas atmosphere.

[0015] Most metal chemicals are very stable at high temperatures, but only Zn 2+ It can be reduced to metallic Zn and then evaporate and diffuse at a temperature above 800° C. Therefore, the present invention uses Zn as an ideal pore-forming template through cations. Zn can also increase the degree of defects in carbon materials and limit the excessive growth of Fe nanoparticles.

[0016] The carbon catalyst prepared by the present invention is to carbonize bacterial cellulose and ZnFe-MOF to produce a hierarchical porous carbon nanofiber block. The hydroxyl functional groups on the bacterial cellulose react with Zn 2+ and Fe 3+ It has a strong affinity and many contact active sites, and then reacts with Zn during pyrolysis. 2+ Gasification and evaporation etching are performed to produce controllable defects and micropores and mesopores in the derived carbon materials. Zn 2+ The voids created during the gasification process further limit the growth of the iron particles. The present invention benefits from the controllable defects, micropores and mesopores, and iron particle size, so that the carbon catalyst has a larger specific surface area and provides higher electrocatalytic activity and stability under all pH conditions. The zinc-air battery constructed with the carbon catalyst of the present invention has a higher specific capacity and significant power density, which indicates its excellent overall energy storage performance and can achieve promising practical applications.

[0017] Preferably, the content of bacterial cellulose in step S1 is 0.7%. Different bacterial cellulose contents will affect the pore structure and dispersion degree of the carbon material.

[0018] In step S1 of the present invention, bacterial cellulose is used as a precursor of the carbon material. If the amount added is too much, it will lead to accumulation of pores in the final carbon material, a decrease in the number of active sites and thus a decrease in catalytic activity; if the amount added is too little, the carbon yield during the pyrolysis process is not high, resulting in a waste of resources and a decrease in carbon production, which is not conducive to actual preparation.

[0019] Preferably, the stirring time in the mixed solution is 1-50 minutes.

[0020] In the present invention, zinc nitrate, ferric chloride and organic ligand dimethylimidazole are slightly soluble in water, and metal ions and organic ligands enter each other's system by diffusion, and a self-assembly reaction occurs to obtain a bacterial cellulose and MOF mixed material.

[0021] More preferably, the stirring time in step S2 is 20 minutes, so that the two can be completely and evenly mixed with the bacterial cellulose in the water.

[0022] Preferably, the freeze-drying time in step S3 is 12-48 hours.

[0023] Preferably, the pyrolysis temperature in step S4 is 700-1000° C. and the time is 1-3 h.

[0024] More preferably, the pyrolysis temperature is 900° C. and the time is 2 h.

[0025] More preferably, the pyrolysis is performed in an inert atmosphere such as nitrogen or argon.

[0026] The present invention also provides the use of the carbon catalyst in a zinc-air battery, and the carbon catalyst is used as a cathode electrode material in the zinc-air battery.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention uses bacterial cellulose as the skeleton and carbon source, and utilizes Zn 2+ Gasification and evaporation etching produce a large number of defects and a large number of micropores and mesopores, which limit the further growth of metallic iron particles. Then, through the optimization of drying and high-temperature carbonization processes, a carbon catalyst with high specific surface area and high catalytic activity in the full pH range is obtained, thereby providing a battery cathode material with excellent electrochemical performance.

[0029] 2. The method of the present invention effectively enhances the structural stability and active sites of the carbon catalyst, making it have good cycle stability and high catalytic activity.

[0030] 3. The present invention uses biomass-based carbon catalysts in zinc-air batteries as cathode electrode materials to produce zinc-air batteries with high specific capacitance and high power density.

[0031] 4. The method of the present invention is simple and controllable, has good repeatability, is easy to industrialize, and can be promoted and applied in the field of green energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 TEM and EDS images of the carbon catalyst prepared in Example 1.

[0033] Figure 2 The rotating disk-ring-disk electrode polarization curve / ORR activity diagram of the carbon catalyst of Example 1 and the commercial reference sample Pt / C in 0.1 M KOH electrolyte.

[0034] Figure 3Graph showing the rotating disk-ring-disk electrode polarization curves / ORR activity of the carbon catalyst of Example 1 and the commercial reference sample Pt / C in 0.5 M H2SO4 electrolyte.

[0035] Figure 4 The rotating disk-ring-disk electrode polarization curve / ORR activity diagram of the carbon catalyst of Example 1 and the commercial reference sample Pt / C in 0.1 M PBS electrolyte.

[0036] Figure 5 This is a graph of the power density of the zinc-air battery assembled in 6M KOH electrolyte in Example 1.

[0037] Figure 6 This is a power density diagram of the zinc-air battery assembled in Example 1 in a 4M NH4Cl+2M KCl mixed electrolyte. DETAILED DESCRIPTION

[0038] The technical scheme of the present invention is further described below by specific embodiments. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in this area, and the methods used in the embodiments are all conventional methods in this area. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention.

[0039] Embodiment 1:

[0040] S1: Add 25 mL of bacterial cellulose dispersion, wash thoroughly with deionized water, and redisperse in a mixed solution of tert-butyl alcohol and water;

[0041] S2: Add 255.8 mg zinc nitrate, 50 mg ferric chloride and 2824.6 mg dimethylimidazole to the above solution;

[0042] S3: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0043] S4: Heat to 900℃ at a rate of 5℃ / min, keep warm for 2h, take out the tube resistance furnace after cooling, and obtain a specific surface area of ​​704m 2 g -1 , pore volume is 0.6cm 3 g -1 , carbon catalyst with a pore size of 4.81nm.

[0044] Embodiment 2:

[0045] S1: Add 25 mL of bacterial cellulose dispersion, wash thoroughly with deionized water, and redisperse in a mixed solution of tert-butyl alcohol and water;

[0046] S2: Add 50 mg of ferric chloride and 2824.6 mg of dimethylimidazole to the above solution;

[0047] S3: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0048] S4: Heat to 900℃ at a rate of 5℃ / min, keep warm for 2h, take out the tubular resistance furnace after cooling, and obtain a specific surface area of ​​119m 2 g -1 , pore volume is 0.1cm 3 g -1 , carbon catalyst with a pore size of 15.81nm.

[0049] Embodiment 3:

[0050] S1: Add 25 mL of bacterial cellulose dispersion, wash thoroughly with deionized water, and redisperse in a mixed solution of tert-butyl alcohol and water;

[0051] S2: Add 255.8 mg zinc nitrate, 35 mg ferric chloride and 2824.6 mg dimethylimidazole to the above solution;

[0052] S3: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0053] S4: Heat to 900℃ at a rate of 5℃ / min, keep warm for 2h, take out the tubular resistance furnace after cooling, and obtain a specific surface area of ​​525m 2 g -1 , pore volume is 0.5cm 3 g -1 , carbon catalyst with a pore size of 6.72nm.

[0054] Embodiment 4:

[0055] S1: Add 25 mL of bacterial cellulose dispersion, wash thoroughly with deionized water, and redisperse in a mixture of tert-butyl alcohol and water:

[0056] S2: Add 255.8 mg zinc nitrate, 65 mg ferric chloride and 2824.6 mg dimethylimidazole to the above solution;

[0057] S3: Pre-freeze in liquid nitrogen for 24 hours, and then dry in a vacuum freeze dryer for 48 hours;

[0058] S4: Heat to 900℃ at a rate of 5℃ / min, keep warm for 2h, take out the tubular resistance furnace after cooling, and obtain a specific surface area of ​​325m 2 g -1 , pore volume is 0.3cm 3 g-1 , carbon catalyst with a pore size of 9.72nm.

[0059] The carbon material sample of the metal organic framework material obtained in Example 1 was scanned using a transmission electron microscope to characterize its morphology and structure. Figure 1 It can be seen that the carbon material prepared in Example 1 has a rich chemical structure, densely arranged nanopores, and a dense graphitized carbon layer with high conductivity. The iron nanoparticles are small in size, about 10-50nm. EDS results show successful doping of iron and nitrogen elements. It can be seen that the prepared carbon catalyst has a large pore structure and conductivity.

[0060] The carbon catalysts obtained in Example 1 and Example 2, 3, and 4 were used as oxygen reduction reaction, named A, B, C, and D, respectively, and coated on a rotating disk electrode. In a three-electrode system, the Hg / HgO electrode was used as a reference electrode, the stone mill rod electrode was used as a counter electrode, and a 0.1M KOH solution was used as an electrolyte, and its electrochemical performance was tested at room temperature.

[0061] Figure 2 The rotating disk-ring-disk electrode polarization curve / ORR activity diagram of the carbon catalyst of Example 1 in 0.1 M KOH electrolyte and the commercial reference sample Pt / C shows that the carbon catalyst obtained in Example 1 has a more positive half-wave potential and a larger current density, indicating that the catalyst has a higher catalytic activity.

[0062] Figure 3 The rotating disk-ring-disk electrode polarization curve / ORR activity diagram of the carbon catalyst of Example 1 in 0.5M H2SO4 electrolyte and the commercial reference sample Pt / C shows that the carbon catalyst obtained in Example 1 has a half-wave potential and a larger current density than those of commercial Pt / C, indicating that the catalyst has good catalytic activity in acidic media.

[0063] Figure 4 The rotating disk-ring-disk electrode polarization curves / ORR activity diagrams of the carbon catalyst of Example 1 in 0.1M PBS electrolyte and the commercial reference sample Pt / C show that the carbon catalyst obtained in Example 1 has a half-wave potential and a larger current density than those of commercial Pt / C, indicating that the catalyst has good catalytic activity in a neutral medium.

[0064] Figure 5 The power density diagram of the zinc-air battery assembled in 6M KOH electrolyte shows that the zinc-air battery obtained in Example 1 has a higher power density than commercial Pt / C, indicating that the catalyst-based zinc-air battery has better performance.

[0065] Figure 6The power density diagram of the zinc-air battery assembled in 4M NH4Cl+2M KCl electrolyte shows that the zinc-air battery obtained in Example 1 has a higher power density than commercial Pt / C, indicating that the catalyst-based zinc-air battery exhibits excellent performance under a neutral environment.

[0066] It can be seen from the above results that compared with the oxygen reduction performance of biomass-based carbon catalysts in the prior art, the method of the present invention effectively increases the pore structure of the prepared carbon catalyst and the size of the metal particles, and increases the types and number of active sites. The selection of suitable biomass bacterial cellulose as a carbon source, plus an appropriate amount of metal elements, and the optimization of the pore structure through simple stirring, drying and high-temperature carbonization processes not only effectively enhances the specific surface area of ​​the carbon material and introduces adjustable defects, but also provides electrocatalytic performance under full pH conditions for zinc-air batteries, which can be used for the preparation of green energy storage devices with high specific capacitance, long cycle life and high energy density.

[0067] The parts of the embodiments herein that are not exhaustive of the midpoint values ​​of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.

[0068] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

[0069] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A method for preparing an iron-nitrogen-doped carbon catalyst having a full pH range, characterized in that: The specific surface area of ​​the carbon catalyst is 186-704m 2 g -1 , pore volume is 0.10-0.6cm 3 g -1 , pore size is 5-10nm.

2. The iron-nitrogen-doped carbon catalyst with a full pH range according to claim 1, characterized in that: The specific surface area of ​​the carbon catalyst is 700-710m 2 g -1 , pore volume is 0.50-0.60cm 3 g -1 , the pore size is 5-6nm.

3. An iron-nitrogen-doped carbon catalyst with a full pH range as claimed in claim 1, characterized in that: The method comprises the following steps: S1: preparing bacterial cellulose dispersion; S2: adding ferric chloride, zinc nitrate and dimethylimidazole into the bacterial cellulose dispersion and stirring evenly; S3: centrifugal freeze drying to obtain solid powder; S4: High temperature pyrolysis under an inert protective gas atmosphere.

4. The iron-nitrogen-doped carbon catalyst with a full pH range according to claim 1, characterized in that: The bacterial cellulose content in step S1 is 0.7%.

5. The iron-nitrogen-doped carbon catalyst with a full pH range according to claim 1, characterized in that: The stirring time in the mixed solution of step S2 is 20 minutes.

6. The iron-nitrogen-doped carbon catalyst with a full pH range according to claim 1, characterized in that: The freeze-drying time in step S3 is 12-48 hours.

7. The iron-nitrogen-doped carbon catalyst with a full pH range according to claim 1, characterized in that: The carbonization temperature in step S4 is 700-1000° C., and the carbonization time is 1-3 hours.

8. A use of an iron-nitrogen doped carbon catalyst with a full pH range as claimed in claim 1 in a zinc-air battery, characterized in that: The iron-nitrogen doped carbon catalyst with a full pH range as claimed in any one of claims 1 to 7 is used in a zinc-air battery.

Citation Information

Cited By

  • Self-supporting composite electrode for CDI as well as preparation method and application of self-supporting composite electrode

    CN120441037A